Philosophical And Ethical Analysis Of The Causes And Harmful Consequences Of Child Marriage (Eurasian Journal of Humanities and Social Sciences, 2024)
The mental, spiritual and physical perfection of the two parties entering into marriage is definitely the foundation of family stability and the formation of a healthy lifestyle in society. Among people who are ready to get married in every way, we can see children with a healthy lifestyle and moral qualities growing up on the basis of a contract. But no matter how sad it is, child marriage has been seen as normal throughout human history. We are witnessing this type of marriage in some regions of our country together with the nations of the world. In the article, we present the results of our research on the causes of underage marriage and its harmful effects on the family and society.